(untitled) (Annals of Medical Research, 2021)
Aim: Preoperative biliary drainage is suggested for patients with jaundice, considering that surgical operations may increase postoperative complications in the presence of jaundice. The aim of this study was to test the effect of biliary drainage on possible serious complications, deaths, or period of hospital stay.Material and Methods: Between January 2012 and June 2016, 160 patients with operable and resectable periampullary tumors who were diagnosed with periampullary tumors underwent pancreaticoduodenectomy (Whipple’s procedure) in Marmara University Pendik Training and Research Hospital, Department of General Surgery. The patients’ demographics, accompanying comorbid diseases, type of biliary drainage, drainage duration, pre- and post-drainage laboratory data, emerging complications and need for re-hospitalization were recorded retrospectively from the accessible files and records.Results: It was observed that out of 158 patients with periampullary tumors, 116 that were operated with drainage had a higher occurrence of surgical site infections and anastomotic leaks, compared to the 42 patients that were operated without drainage. Similarly, when patient results were classified according to the Clavien-Dindo complication classification, the ratio was again against the patients that were operated with drainage. Drainage patients stayed in the hospital for a longer period; however, in terms of pancreatic fistula, re-hospitalization, need for intensive care and relaparotomy ratios, and especially in terms of mortality ratios, a difference between two patient groups was not observed. Conclusion: Investigating the data collected from patients that were operated without drainage, and specifically considering the bilirubin values of the patients who had complications, there was no threshold identified that contributed to a higher likeliness of complications. Consequently, even though there were no results to motivate recommending drainage, it was concluded that applying drainage does not create any difference in short-term prognosis, but drainage increases infectious complications.Keywords: Periampullary cancer; obstructive jaundice; preoperative biliary drainage; postoperative complication; hyperbilirubinemia.